Fast and Quantitative NMR Metabolite Analysis Afforded by a Paramagnetic Co‐Solute. (11th September 2019) - Mulder, Frans A. A.; Tenori, Leonardo; Luchinat, Claudio
Abstract: NMR spectroscopy is an indispensable technique for the determination of the chemical identity and structure of small molecules. The method is especially recognized for its robustness and intrinsically quantitative nature, and has manifested itself as a key analytical platform for diverse fields of application, ranging from chemical synthesis to metabolomics. Unfortunately, the slow recovery of nuclear spin polarization by spin‐lattice (T1 ) relaxation causes most experimental time to be lost on idle waiting. Furthermore, truly quantitative NMR (qNMR) spectroscopy requires waiting times of 5‐times the longest T1 in the sample, making qNMR spectroscopy slow and inefficient. We demonstrate here that co‐solute paramagnetic relaxation can mitigate these two problems simultaneously. The addition of a small amount of paramagnetic gadolinium chelate, available in the form of commercial contrast‐agent solutions, enables cheap, quantitative, and efficient high‐throughput mixture analysis. Abstract : Sowohl als auch ! Die inhärent quantitative Natur der NMR‐Spektroskopie wird meist zugunsten hoher Empfindlichkeit aufgegeben. Hier wird gezeigt, dass die Analyse von Mischungen durch NMR‐Spektroskopie sowohl quantitativ als auch zeiteffektiv ist, wenn die Relaxationsverstärkung einer paramagnetischen Substanz, in Form eines kommerziell verfügbaren Gadolinium‐Chelats, genutzt wird.